Ten thousand children : true stories told by children who escaped the Holocaust on the Kindertransport - Fox, Anne L. 1926- (Behrman House, 1999)
Tells the true stories of children who escaped Nazi Germany on the Kindertransport, a rescue mission led by concerned British to save Jewish children from the Holocaust